Antimalarial Efficacy of Ethanol Extract of Bridelia micrantha Stem Bark against Plasmodium berghei-Infected Mice - Tako Djimefo Alex Kevin; Yamssi Cedric; Noumedem Anangmo Christelle Nadia; Tientcheu Noutong Jemimah Sandra; Mounvera Abdel Azizi; Ngouyamsa Nsapkain Aboubakar Sidiki; Gamago Nkadeu Guy-Armand; Mbohou Nchetnkou Christian; Essangui Same Estelle Géraldine; Tankoua-Tchounda Roméo; Vincent Khan Payne; Lehman Léopold Gustave (Journal of Parasitology Research)
Background. The spread of drug resistance is a significant issue, particularly in endemic countries with limited resources. The aim of this study was to evaluate antimalarial and antioxidant activity of B. micrantha in order to justify its use in traditional medicine. Methods. Evaluation of the in vivo antimalarial activity of B. micrantha was carried out according to the model of the suppressive and curative test of Peters’ over 4 days in infected Swiss albino mice. Antioxidant parameters and stress were measured after intraperitoneal administration of 1×107 infected red blood cells. Results. At doses of 150 mg/kg, 300 mg/kg, and 600 mg/kg, administration of B. micrantha substantially produced suppression of P. berghei infection by 67.75%, 73.46%, and 78.99%, respectively, while 84.64% of the untreated group (1% DMSO) had suppression from chloroquine. The curative test significantly decreased the levels of parasitaemia and death in the treated groups. Furthermore, after B. micrantha extract was given to infected mice, a noteworthy increase in total protein, aspartate aminotransferase (AST), and alanine aminotransferase (ALT) was observed. On the other hand, hepatic catalase (CAT) and superoxide dismutase (SOD) productions were considerably greater than that of the healthy control. Mice had considerably lower levels of nonenzymatic antioxidant markers such as glutathione, NO, and MDA showing that the liver was protected. Conclusion. The infected groups responded favorably to the ethanol extract of B. micrantha. This result justifies investigation for its use in Cameroon.